Analysing The Role of Lifestyle Factors on Hypertension Among Rural Indonesian Adults: A Case-Control Study - Nurbaiti; Nur Nasry Noor; A Arsunan Arsin; Andi Zulkifli; Arifin Seweng; Suryani Tawali (Medsci Publications, 2024)
Background: Hypertension is a degenerative disease, arising from unhealthy lifestyle and becoming a world health problem. It is estimated that 46% of adults with hypertension are unaware of their condition, hence it is called the "silent killer". This study aims to Lifestyle Risk Factors of Hypertension Incidence upon Productive Age. Methodology: The type of research used was analytical observational with case control design the samples in this study were 152 (76 cases and 76 controls). The sampling technique in this research was probability sampling using systematic random sampling. Data were processed using Stata version 14 program. The analysis performed was chi-square test and logistic regression test. Results: The results showed exposure to cigarette smoke (OR= 3.398; 95%CI=1.540-7.683), alcohol consumption (OR= 4.277; 95%CI=1.608-12.606), sleep patterns (OR= 2.628; 95%CI=1.299-5.337), physical activity (OR= 1.75; 95%CI=0.824-3.746), stressful state (OR= 1.793; 95%CI=0.897-3.590;), and coffee consumption (OR= 1.258; 95%CI=0.613- 2.587;). In multivariate analysis, the most risk factor for hypertension was alcohol consumption (OR=4.948; 95%CI=1.841-13.302; ρ-value =0.002). Conclusions: Risk factors for hypertension included exposure to cigarette smoke, alcohol consumption and sleep patterns and the most risk factor for hypertension was alcohol consumption. It is highly suggested that relevant stake holders to determine programs and policies in order to prevent and treat hypertension more effectively.